Impact of COVID-19 on the Use of Emergency Contraceptives in Ghana: An Interrupted Time Series Analysis - Fuseini, Kamil; Jarvis, Leah; Hindin, Michelle J.; Issah, Kofi; Ankomah, Augustine (Frontiers in Reproductive Health, 2022)
The COVID-19 pandemic has disrupted reproductive health services including decline in the use of pre-coital contraceptives. However, evidence of its impact on the use of emergency contraceptives (ECs), often, a post-coital method, is limited in the emerging literature on the impact of COVID-19 on contraception, hence this study. Data on total number of EC users from January 2018 to February 2020 (pre-COVID-19) and March to December 2020 (during COVID-19) were extracted from the Ghana Health Service District Health Information Management System. Interrupted Time Series analysis was used to estimate the impact of COVID-19 on the trend of EC use, adjusting for serial autocorrelation and seasonality. The results showed a gradual upward trend in EC use before the pandemic, increasing at a rate of about 67 (95% CI 37.6-96.8; p=0.001) users per month. However, the pandemic caused a sudden spike in the use of ECs. The pandemic and its related restrictions had an immediate effect on the use of ECs, increasing significantly by about 1939 users (95% CI 1096.6-2781.2; p=0.001) in March 2020. Following March 2020, the number of EC users continued to increase, on average by about 385 users per month (95% CI 272.9-496.4; p=0.001). Unlike pre-coital contraceptive methods, the evidence shows that use of ECs, often used as a post-coital method for unprotected sex was not negatively impacted by the COVID-19 pandemic. In fact, it is the opposite. Hence, in planning for similar situations more attention should be given to the distribution of post-coital contraceptive methods.